Combustion synthesis as a low temperature route to Li4Ti5O12 based powders for lithium ion battery anodes. Issue 30 (29th March 2017) - De Sloovere, Dries; Marchal, Wouter; Ulu, Fulya; Vranken, Thomas; Verheijen, Maarten; Van Bael, Marlies K.; Hardy, An
Abstract : An LTO based anode material was synthesized at a significantly lower temperature and shorter processing time than previously reported. Abstract : Spinel Li4 Ti5 O12 (LTO) is considered as a promising anode material for lithium ion batteries due to its high stability and its inherent safety. Since LTO is typically synthesized at high temperatures, a study of combustion synthesis of LTO is presented, wherein effects of oxidizer amount in the precursor and atmosphere during thermal decomposition are investigated. Combustion synthesis implies heating a precursor to a relatively low process temperature, after which the system generates the necessary energy for complete conversion and crystallization to the desired oxide. Hereto, the precursor and thermally treated powders were characterized by thermogravimetric analysis (TGA) coupled with differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), dynamic light scattering (DLS), X-ray diffraction (XRD), cyclic voltammetry (CV) and galvanostatic cycling. The study shows that the combustion process allows the synthesis of LTO at process temperatures as low as 300 °C, compared to around 800 °C for solid state reactions and sol–gel routes. The product consists of crystalline LTO with minor impurities. The product was used as an electrode material in a lithium battery coin cell and demonstrated a high stability and a capacity of 164 mA h g −1 at 0.1C and 132 mA h g −1 at 2C. This paper shows that combustion synthesis can considerably lower the temperature required for the synthesis of ceramic materials, after careful optimization of the precursor, since the mechanism of thermal degradation is complex and dependent on a large number of parameters.